O-069 Effect of intravenous thrombolysis before endovascular therapy on outcomes in patients with large core infarct: insight from the STAR registry. (23rd July 2022) - Anadani, M; Shaban, A; Al Kasab, S; Chalhoub, R; Maier, I; Psychogios, M; Alaweih, A; Wolfe, S; Authur, A; Dumont, T; Kan, P; Kim, J; et al.
Abstract : Background: The utility of intravenous thrombolysis (IVT) before mechanical thrombectomy (MT) remains a matter of debate. The data regarding the safety and efficacy of IVT prior to MT in patients with large core infarct is scarce. Objective: To compare the functional and safety outcomes between patients with large core infarct due to LVO treated with IVT and MT to those treated with MT alone. Methods: This is a retrospective analysis of the Stroke Thrombectomy Aneurysm Registry (STAR). Large core infarct was defined as Albert Stroke Program Early CT Score (ASPECTS) ≤5. Patients with large core infarct due to anterior circulation large vessel occlusion (internal carotid artery occlusion, M1 segment occlusion, or tandem occlusion) treated with MT were enrolled in this study. Patients were divided into two groups based on pretreatment intravenous thrombolysis (IVT+, IVT-). The association between IVT and favorable outcome (mRS 0–2) or significant intracranial hemorrhage (PH2 or sICH) was assessed using a logistic regression model adjusted for age, sex, admission NIHSS, onset to groin time, and pre-stroke mRS. Results: Of 6151 patients enrolled in the STAR registry during the study period, 398 patients (mean age 67.5 14 years, median NIHSS 19, median onset to groin 321 minutes) met our inclusion criteria and were included in the final analysis. Favorable outcome was achieved in 27.3%, and 17.4% in the IVT+ and IVT- groups (p=0.027), respectively. Significant ICH (sICH or PH2) occurred in 16.9% and 13.1% in the IVT+ and IVT- groups (p-0.26), respectively. In an adjusted logistic regression model, IVT was not associated with favorable outcomes (OR, 1.78; 95% CI 0.91–3.48) or significant hemorrhage (OR, 1.36; 95% CI 0.71–2.59). Conclusion: Patients with large core infarct due to large vessel occlusion treated with intravenous thrombolysis and mechanical thrombectomy had comparable outcomes to those treated with mechanical thrombectomy alone. Disclosures: M. Anadani: None. A. Shaban: None. S. Al Kasab: None. R. Chalhoub: None. I. Maier: None. M. Psychogios: None. A. Alaweih: None. S. Wolfe: None. A. Authur: None. T. Dumont: None. P. Kan: None. J. Kim: None. R. De Leacy: None. J. Osbun: None. A. Rai: None. P. Jabbour: None. M. Park: None. J. Mascitelli: None. M. Levitt: None. A. Polifka: None. W. Casagranda: None. S. Yoshimura: None. C. Matouk: None. R. Williamson: None. B. Gory: None. M. Mokin: None. I. Fragata: None. D. Romano: None. S. Chowdry: None. M. Moss: None. D. Behme: None. K. Limaye: None. A. Spiotta: None. E. Samaniego: None.